Research progress on the mechanism of kidney proximal tubule NHE3 in the angiotensin Ⅱ-dependent hypertension - LI Xiaochun; ZHUO Jialong; ZHENG Xiaowen; ZHAO Chunling; ZHANG Jianfeng; JIANG Yueming (Guangxi Yike Daxue xuebao)
Hypertension is a multifactorial disorder involving genetic susceptibility, neuroendocrine dysregulation, cardiovascular and kidney dysfunction, and dietary factors. One of the most studied factors contributing to normal blood pressure control and the development of hypertension is sodium (Na+) intake and salt sensitivity. Studies in clinical, epidemiological, and genetic animal models have shown a close relationship between Na+ intake and blood pressure, with excessive Na+ intake particularly associated with hypertension in blacks, elderly and those with chronic kidney disease. The balance between Na+ intake and excretion is primarily regulated by small intestines of the gastrointestinal tract and the proximal and distal tubules of kidneys. The Na+ and hydrogen (H+) exchanger 3 (NHE3), member 3 of solute carrier family 9 (SLC9A3), plays a crucial role in mediating active transcellular Na+ and bicarbonate reabsorption in the proximal tubules of the small intestine and kidneys. However, the role and mechanism of NHE3 in small intestines and proximal tubules of the kidneys in normal blood pressure regulation and the pathogenesis of hypertension have not been well studied. Recently, the research group of this project utilized novel genetically modified whole-body, kidney, and proximal tubule-specific NHE3 knockout mouse models to investigate the critical role and mechanisms of intestinal and kidney proximal tubular NHE3 in maintaining basal blood pressure homeostasis and in the development of angiotensin Ⅱ-induced hypertension. These new findings not only support the critical roles of intestinal and kidney proximal tubular NHE3 in maintaining normal blood pressure and in the development of angiotensin Ⅱ-dependent hypertension, but also provide potential new therapeutic targets for treating poorly controlled hypertension in humans.